Transformation des sentiments et développement du pouvoir d’agir - Nadine Poussin (Perspectives Interdisciplinaires sur le Travail et la Santé)
Using the results of an intervention conducted from an activity clinic perspective with occupational health physicians, this study explored the links between mime on the one hand and, on the other, physicians’ adaptation of emotions and development of their capacity to act on their environment. The intervention was used to confront professionals with their own work activity and that of their peers, and thereby to generate a discussion that allowed them to go over arguments for and against specific procedures. We concluded that although the physicians were initially affected, embarrassed, and taken aback by the analysis of their work activity, this destabilization was productive in that it led them to discuss the goals of their actions and to reflect upon the relationships between the goals and motives of their work activity. We saw these as the conditions needed to adapt their emotions and develop the capacity to act on their environment.